Efficacy of cognitive behavioral therapy for insomnia (CBT-I) in older adults with insomnia: A systematic review and meta-analysis. (October 2022) - Huang, Kexin; Li, Su; He, Rendong; Zhong, Tangsheng; Yang, Haiqi; Chen, Li; Gao, Hui; Jia, Yong
Objectives: The aim is to evaluate the efficacy of cognitive behavioral therapy for insomnia (CBT-I) in older adults. We searched six databases to identify articles published in English or Chinese until January 30 th, 2022.Methods: The two authors of the review independently selected the studies, assessed the risk of bias, and extracted the data. Fourteen studies were included.Results: Based on the results from sleep logs, a significant pooled effect size was observed for sleep efficiency (SE%) (MD = 8.36; 95% CI, 5.96–10.76; I 2 = 77%; p < .00001), sleep onset latency (SOL) (MD = −9.29; 95% CI, −13.62 to −4.96; I 2 = 64%; p < 0.0001), wake after sleep onset (WASO) (MD = −23.44; 95% CI, −32.41 to −14.47; I 2 = 85%; p < .00001), and total sleep time (TST) (MD = −12.35; 95% CI, −21.27 to −3.42; I 2 = 63%; p = 0.007).Conclusions: Our study suggests that CBT-I may be a safe and effective approach for improving insomnia in older adults.